Best practices in achieving patient diversity in oncology clinical trials. Issue 28 (1st October 2022) - Curry, Andrea; Vidal, Gregory A.; Greener, Judith R
Abstract : 87 Background: The underrepresentation of Black patients in cancer clinical trials in the United States has been well documented. While a multitude of recommendations exist from government organizations, academic institutions, industry sponsors, and commercial groups on approaches designed to increase enrollment, there is a lack of evidence as to the effectiveness of these recommendations in real-world settings. The West Cancer Center & Research Institute (WCCRI), a community oncology center in the greater Memphis, TN area, has consistently conducted trials in which Black patients are well-represented. Of all oncology clinical trials conducted at WCCRI in 2021, Black patients represented 29.9% of the total enrolled population. To further extend the literature on successful methods to achieve greater trial diversity, enrollment tactics used by WCCRI were explored to understand best practices and assess scalability to other oncology centers. Methods: A total of 35 qualitative in-depth interviews were conducted with multiple constituencies associated with WCCRI to obtain a holistic view of clinical trial practices. Interviews were held between March and April 2022. Included were Black patients who participated in a clinical trial, Black patients that declined participation in a clinical trial, caregivers of these patients, WCCRI staff, and community leaders in the Memphis, TN area. All patients interviewed had a history of solid malignancies and were treated at WCCRI between January 2018 and December 2021. The study was considered minimal risk research and all participants provided informed consent before study participation. Results: This research underscored the fact that barriers to enroll Black patients are complex and involve challenges at various structural levels including the system, individual, and interpersonal levels. WCCRI practices were found to incorporate tactics at each of these levels, leading to the ability of this community oncology center to enroll representative proportions of Black patients into its oncology trials. Examples of tactics that reach into the community include coordinating with local leaders to provide residents with health education; outreach by Black WCCRI staff, diverse PIs, and ambassadors to dispel myths about a cancer diagnosis and treatment; and faith-based leaders guiding patients to helpful resources and supportive services provided by WCCRI. Conclusions: Results of this research build upon previous literature that suggest although some success has been identified through interventions at any one level, the greatest opportunity for achieving diversity in oncology trials comes from multilevel interventions. Emphasis should be placed on crafting tactics that simultaneously address factors in each of these levels to consistently achieve enrollment diversity.